Ciclo econômico e política fiscal brasileira no período 2008-2019 - Ness, Mosar Leandro (Universidade do Vale do Rio dos Sinos, 2022)
Economic cycles represent the oscillations of variables, such as production and employment in a sector, region or country. They are presented in a unique, non-divisible form and with their own characteristics in terms of amplitude and duration. The Brazilian economy, over the last two decades, has shown a pronounced cyclical behavior. The origin of such a situation may be related to the conduct of economic policy, as it may have a pro- or counter-cyclical character. Thus, the objective of this thesis was to analyze the economic cycle of Brazil, in the period 2008-2019, in relation to fiscal policy. One of the problems with working with time series is that, in most cases, these series have points outside the curve. Such a situation can lead to estimation errors. To correct this problem, the local-level State Space Model was used. To verify the cyclical behavior, one of the promising techniques is the Regime Change Model. With the seminal work of Hamilton (1989), a new field of investigation related to the topic was opened. In this study, the technique of Markovian Regime Change with Dynamic Regression (MS-DR) was used. The tested hypotheses presented results as expected. The hypothesis of the existence of a common movement between the two series was confirmed. The result made it clear that, in the long term, the behavior of the series is similar, especially with the removal of irregularities. The proposition that the Discretionary Expenses movement is the inductor of the IBC-BR movement was also confirmed.
Keywords: Ciclo econômico; Estado de espaço; Mudança de regime; Política fiscal; Despesa discricionária; Economic cycle; State of space; Regime change; Fiscal policy; Discretionary expenditure; ACCNPQ::Ciências Sociais Aplicadas::Economia